Nature Scenes Counter Mental Fatigue-Induced Performance Decrements in Soccer Decision-Making - Sun, He; Soh, Kim Geok; Xu, Xiaowei (Frontiers in Psychology, 2022)
Background It has been well investigated that nature exposure intervention can restore directed attention and improve subsequent cognitive performance. The impairment of decision-making skills in mentally fatigued soccer players was attributed to the inability of attention allocation. However, nature exposure as the potential intervention to counter mental fatigue and improve the subsequent decision-making skill in soccer players has never been investigated. Objects This study aimed to evaluate the effects of nature exposure intervention on decision-making skills among mentally fatigued university soccer players. Moreover, different durations of nature exposure were also evaluated. Methods A random control between-subject design was adopted. Players were randomly assigned into six groups with three different durations of the experimental group compared to the corresponding control group (4.17 min: Exp 1 vs. Con 1; 8.33 min: Exp 2 vs. Con 2; and 12.50 min: Exp 3 vs. Con 3). All players were first mentally fatigued by performing a 45 min Stroop task; then they viewed virtual photos of natural or urban scenes; and finally, they performed a soccer decision-making task. Results The subjective ratings of mental fatigue were significantly higher following the Stroop task. Only the Exp 3 (12.50 min viewing natural scenes) significantly improved decision-making reaction time compared to Con 3 (p = 0.09). Moreover, the accuracy slightly increased in Exp 3 after the intervention. Conclusion In line with attention restoration theory, nature exposure significantly improved decision-making skills in mentally fatigue university players. However, the duration must be 12.50 min and for each stimulus to stay longer to attract involuntary attention.